Implementation of the KPUâ€™s Role in the 2024 Regional Elections in East Java - I Made Arie Widyasthana Wartana Putra; Almer Rasyid; Rycko Wirawan; Halimatusa Bana; Refa Amalia Cahyani; Tirta Amirella; Amalia Eka Didik Prasetyo (Universitas Tribhuwana Tungga Dewi, 2025)
This article explores the strategic efforts of the General Elections Commission (KPU) in preparing for the 2024 Regional Elections (Pilkada), with a focus on improving procedures and preventing issues experienced in previous elections. Using a literature review method with a narrative synthesis approach, the study analyses data from credible databases such as Google Scholar, Scopus, and Science Direct. Findings highlight that political education initiatives, such as the â€œKPU Goes to Schoolâ€ and â€œKPU Goes to Campusâ€ programs, play a critical role in fostering early political awareness and boosting participation among first-time voters. The KPU's supervision strategy encompasses internal monitoring and close coordination with the Election Supervisory Body (Bawaslu) to address violations and maintain electoral integrity. In East Java, particular emphasis is placed on validating voter data due to the region's size and complexity. Furthermore, participatory programs and technology-based innovations are employed to enhance transparency and uphold the credibility of the electoral process. The study concludes that the KPU's comprehensive oversight, strategic collaboration with Bawaslu, and active public engagement are fundamental in ensuring a fair, transparent, and dignified 2024 Pilkada. These efforts collectively strengthen the democratic process and contribute to more accountable local governance in Indonesia.Artikel ini mengeksplorasi upaya strategis Komisi Pemilihan Umum (KPU) dalam mempersiapkan Pemilihan Umum Kepala Daerah (Pilkada) 2024, dengan fokus pada perbaikan prosedur dan pencegahan masalah yang dialami pada pilkada sebelumnya. Menggunakan metode tinjauan literatur dengan pendekatan sintesis naratif, studi ini menganalisis data dari basis data kredibel seperti Google Scholar, Scopus, dan Science Direct. Temuan menyoroti bahwa inisiatif pendidikan politik-seperti program â€œKPU Masuk Sekolahâ€ dan â€œKPU Masuk Kampusâ€-memainkan peran penting dalam menumbuhkan kesadaran politik sejak dini dan meningkatkan partisipasi di kalangan pemilih pemula. Strategi pengawasan KPU mencakup pengawasan internal dan koordinasi erat dengan Badan Pengawas Pemilu (Bawaslu) untuk mengatasi pelanggaran dan menjaga integritas pemilu. Di Jawa Timur, penekanan khusus diberikan pada validasi data pemilih karena ukuran dan kompleksitas wilayahnya. Selain itu, program partisipatif dan inovasi berbasis teknologi digunakan untuk meningkatkan transparansi dan menegakkan kredibilitas proses pemilu. Penelitian ini menyimpulkan bahwa pengawasan komprehensif KPU, kolaborasi strategis dengan Bawaslu, dan pelibatan publik secara aktif sangat penting untuk memastikan Pilkada 2024 yang adil, transparan, dan bermartabat. Upaya-upaya ini secara kolektif memperkuat proses demokrasi dan berkontribusi pada tata kelola pemerintahan daerah yang lebih akuntabel di Indonesia.